KOMPARASI PENGELOLAAN TANAMAN JAGUNG SISTEM OLAH TANAH SEMPURNA DENGAN SISTEM TANPA OLAH TANAH (TOT) DI KABUPATEN OKU TIMUR - Sugeng Supriyanto (Jurnal Bakti Agribisnis, 2016)
The objectives of this research are: (1) To know the income of corn farmer farmers between the perfect soil system with TOT system in OKU Timur Regency, (2) To know the comparison of management of maize plant between the perfect soil system and the system (TOT) in Kabupaten OKU Timur, (3) To determine the feasibility level of corn cultivation business between a perfect soil system and TOT system in East OKU Regency. This research was conducted in OKU Timur Regency. This research was conducted in April 2015 until June 2015 with a survey method focused on corn farming practices with either a groundless (TOT) system or a perfect soil system in East OKU district. This study found that the average cost of production for the management of corn business activities with the system Without Sports Land (TOT) of Rp. 11.296.925, - / yr, with a flat fee of Rp. 1.088.896, - / Thn, and variable cost of Rp. 10.208.029, - / yr. Receipt is Rp. 29.139.583, - / Thn then the revenue is Rp. 17,842,658, - / yr (Rp 5,947,553, - / MT or Rp 1,486,888, - / bln). While the average cost of production on corn management business activities with a perfect tillage system of Rp. 12.998.688, - / yr, with a fixed fee of Rp. 1.086.254, - / yr, and variable cost of Rp. 11.912.434, - / yr. While the revenue is Rp. 31.819.792, - / Thn then the income is obtained by Rp. 18.821.104, - / yr (Rp 6.273.701, - / MT or Rp 1,568,425, - / month). The comparative value of corn management business with the landless (TOT) system is Rp. 17.842.658, - / MT. While on the management of corn with a perfect soil system is Rp. 18.821.104, - / MT obtained from the final difference with the cost of production. Thus, there is a difference in income of Rp. 978.446, - / MT (Rp 244,611, - / Month). The management of maize with Soil Extract (TOT) and perfect soil system in East OKU Regency can be said to be profitable and feasible, because the average value is obtained R / C Ratio 2.58 which means> 1 then the business is considered profitable, and Also obtained the value of B / C Ratio 1.58 which means> 0, then the business declared feasible